PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSETS, DAN EARNING PER SHARE TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Putri, Wilda Karisma; Puspita, Erna; Kurniawan, Andy (UNIKA Santo Thomas, 2024)
This research is motivated by the fact that stock returns are the main factor desired by investors when carrying out investment activities in the capital market. In before investing, investors should analyze financial performance the company, in order to get the expected return. To assess company’s financial performance, investors can pay attention to factors that can affect stock returns. The aim of this research is to know the infuence of the current ratio, debt to equity ratio, return on assets and earnings per share on stock returns both partially and simultaneously infrastructure sector companies listed on the Indonesian Stock Exchange period 2020-2023. This research uses a quantitative causality approach. Sample in this research, it was obtained using a purposive sampling method based on predetermined criteria, with a population of 57 sector companies infrastructur, and the number of samples that meet the criteria is a 12 companies. The data analysis method used is multiple linier regression analysis with using IBM SPSS Statistics 23 software. Conclusions from the research results these are (1) Current ratio, debt to equity ratio, return on assets and earning per share partially has a significant effect on stock return in the company infrastructure sector listed on the IDX. (2) Current ratio, Debt to Equity Ratio, Return On Assets dan Earning Per Share simultaneously have a significant effect on stock return in infrastructure sector companies that are flat on the Stock Exchange Indonesian Effect.